Well-Known and Novel Players in Endothelial Dysfunction: Updates on a Notch(ed) Landscape - Francesca Fortini; Francesco Vieceli Dalla Sega; Luisa Marracino; Paolo Severi; Claudio Rapezzi; Paola Rizzo; Roberto Ferrari (Biomedicines, 2021)
Endothelial dysfunction characterizes every aspect of the so-called cardiovascular continuum, a series of events ranging from hypertension to the development of atherosclerosis and, finally, to coronary heart disease, thrombus formation, myocardial infarction, and heart failure. Endothelial dysfunction is the main prognostic factor for the progression of vascular disorders, which responds to drug intervention and lifestyle changes. Virtually all of the drugs used to prevent cardiovascular disorders, such as long-used and new antilipidemic agents and inhibitors of angiotensin enzyme (ACEi), exert an important effect on the endothelium. Endothelial dysfunction is a central feature of coronavirus disease -19 (COVID-19), and it is now clear that life-risk complications of the disease are prompted by alterations of the endothelium induced by viral infection. As a consequence, the progression of COVID-19 is worse in the subjects in whom endothelial dysfunction is already present, such as elderly, diabetic, obese, and hypertensive patients. Importantly, circulating biomarkers of endothelial activation and injury predict the severity and mortality of the disease and can be used to evaluate the efficacy of treatments. The purpose of this review is to provide updates on endothelial function by discussing its clinical relevance in the cardiovascular continuum, the latest insights from molecular and cellular biology, and their implications for clinical practice, with a focus on new actors, such as the Notch signaling and emerging therapies for cardiovascular disease.